PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SUNGAI PENUH - MANDASARI, NANIK (RC-INSTITUT, 2018)
Compensation represent paased to appreaciation is indirect and also direct good officer, financial and also non fair financial to their contribution or officer in reaching the target of organization, so that giving of compensation very required by organization. Cultural of organization represent norm, accepted as by habit and values and truth of by everybody in organization to performance aparatur civil state (ASN). Target of this researt is to know compensation influence and organization culture  to aparatur civil state performance at on duty kependudukan and record-keeping full of civil town river. This research use quantitave approach where obtained data is data spreading of quiesioner field to all responder. From result of research known that compensation do not have influence which is signifikan to performance civil state aparatur (ASN) at on duty kependudukan and record keeping full of civil town river while organization culture have influence which is significant to performance civil state of aparatur (ASN) at on duty kependudukan and record keeping of full of civil town river. From result of calculation by using SPSS analyzer 16.0 where value is 0,625, its meaning of organization culture  and conpensation  have  influence to performance civil state aparatur (ASN) at on duty kependudukan and record keeping of full of civil town river. Result of calculation of compensation determinan coofficent aqual to 60,40 % it’s meaning to not there are compensation influence to performance ASN While it’s side 39,60% explained by other factors. While result of calculation of cultural determinan coefficient of organization equal to 0,10%, it’s meaning there are compensation influence to performance Civil State Aparatur (ASN) while its side 99,90% explained by variable.    Keyword: compensation, cultural of organization and civil state aparatur  (ASN)